Tingkat Prokrastinasi Akademik Siswa Sekolah Menengah Pertama Muhammadiyah 9 Yogyakarta - Munawaroh, Martika Laely; Alhadi, Said; Saputra, Wahyu Nanda Eka (Jurnal Kajian Bimbingan dan Konseling, 2017)
Academic procrastination is one of problems that may occur among junior high school students. This study aims to describe the level of academic procrastination of junior high school students in Sekolah Menengah Pertama Muhammadiyah 9 Yogyakarta. This research uses descriptive quantitative research. The results of this study showed that 17,2% of subjects have high academic procrastination, 77,1% of them have the moderate one, and 5,7% of them have the low one. Based on those results, it is recommended for the next researcher to use Solution-Focused Brief Counseling in reducing academic procrastination in SMP Muhammadiyah 9 Yogyakarta.